Mathematics learning outcomes of IX–X Grades Students are Associated with the Characteristics of Educational Environment - Cibulskaitė, Nijolė; Jurkėnaitė, Gintarė (Pedagogika, 2014)
This paper presents a study carried out for the purpose to highlight the characteristics of social-psychological conditions of educational environment associated with higher math learning outcomes of the IX–Xth form students. The study obtained data allowed to determine teachers’ teaching and learning methods and techniques are related with mathematics learning outcomes, and how they are determined by the nature of mathematics teachers’ communication with students. Higher mathematics learning outcomes are associated with such teachers’ teaching and learning methods and techniques: in the IXth grade – the checking and assessing of classmates’ work, check oneself class work or home work in the group of students, working with a computer at home; in the Xth grade-presentation of elements of the mathematics history. Higher mathematics learning out comes in grade IXth are related with teachers’ attention to student’s interests and emotions in the classroom, with listening to the end, when they are answering, the teachers’ assistance when the students requested it, believing in benevolence and kindness of students, pleas ant interaction with the students, the promotion of students to be dutiful; in the grade X-teachers’ attention to student well-being and interests.